Perspectives of Migrants and Employers on the National Insurance Policy (Health Insurance Card Scheme) for Migrants: A Case Study in Ranong, Thailand - Srisai P; Phaiyarom M; Suphanchaimat R (Dove Medical Press, 2020)
Patinya Srisai,1 Mathudara Phaiyarom,1 Rapeepong Suphanchaimat1,2 1International Health Policy Program (IHPP), The Ministry of Public Health, Nonthaburi 11000, Thailand; 2Division of Epidemiology, Department of Disease Control, The Ministry of Public Health, Nonthaburi 11000, ThailandCorrespondence: Patinya SrisaiInternational Health Policy Program (IHPP), The Ministry of Public Health, 88/20 Satharanasuk 6 Alley, Tambon Bang Khen, Mueang Nonthaburi District, Nonthaburi 11000, ThailandTel +66-2-590-2366Fax +66-2-590-2385Email patinya@ihpp.thaigov.netBackground and Purposes: Thailand has implemented a nationwide insurance policy for migrants, namely the Health Insurance Card Scheme (HICS), for a long time. However, numerous implementation challenges remain and migrant perspectives on the policy are rarely known. The aim of this study was to examine migrant service users’ perspectives and their consequent response towards the HICS.Methods: A qualitative case-study approach was employed. In-depth interviews with ten local migrants and four employers were conducted in one of the most densely migrant-populated provinces in Thailand. Document review was used as a means for data triangulation. Inductive thematic analysis was exercised on interview data.Results: The findings revealed that most migrants were not aware of the benefit, they are entitled to receive from the HICS due to unclear communication and inadequate announcements about the policy. The registration costs needed for legalising migrants’ precarious status were a major concern. Adequate support from employers was a key determining factor that encouraged migrants to participate in the registration process and purchase the insurance card. Some employers sought assistance from private intermediaries or brokers to facilitate the registration process for migrants.Conclusion: Proper communication and promotion regarding the benefits of the HICS and local authorities taking action to expedite the registration process for migrants are recommended. The policy should also establish a mechanism to receive feedback from migrants. This will help resolve implementation challenges and lead to further improvement of the policy.Keywords: migrants, health insurance, health policy, health service user, policy implementation, Thailand